ANALISIS URGENSI PENGEMBANGAN BAHAN AJAR KOMIK DENGAN MENGINTEGRASIKAN KONTEKS KEMARITIMAN - M. Jaya Adi Putra; Mutia Yulita Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The urgency of developing comic-based teaching materials that integrate maritime context arises from the need to enrich educational methods and enhance maritime literacy among students in Indonesia, a country with vast maritime potential. This study aims to explore the importance and effectiveness of comics as an educational tool in delivering maritime-related content to students. Using qualitative methods, including interviews with educators and analysis of students' learning preferences, this research highlights the appeal and effectiveness of visual media in education. Comics, with their engaging and interactive format, have been shown to increase students' motivation and knowledge retention compared to traditional teaching methods. The integration of maritime themes into these teaching materials not only provides educational value but also fosters a deeper understanding of Indonesia's maritime identity and raises awareness of the importance of the maritime sector in the nation's economy, culture, and environment. The study concludes that there is an urgent need for the development of innovative teaching materials that reflect local contexts, such as maritime issues, to better engage students and make learning more relevant to their environment. Furthermore, the successful implementation of such educational tools requires collaboration among educators, policymakers, and comic illustrators, supported by educational policies that encourage the adoption of contextually relevant teaching materials. This approach is crucial for optimizing Indonesia's maritime potential through a more adaptive and responsive education system.